Cognitive Flexibility Mediating the Link Between Perfectionism and Impostor Feelings Among Female Undergraduate Students - Gottschlich, Daniela; Piskorz-Ryń , Oriana (Journal of Personality and Psychosomatic Research (JPPR), 2025)
This study aimed to examine the mediating role of cognitive flexibility in the relationship between perfectionism and impostor feelings among female undergraduate students in Canada. A descriptive correlational research design was employed with a total sample of 400 female undergraduate students selected through stratified random sampling based on the Morgan and Krejcie (1970) table. Standardized self-report instruments were used: the Frost Multidimensional Perfectionism Scale (FMPS; Frost et al., 1990) to assess perfectionism, the Cognitive Flexibility Scale (CFS; Dennis & Vander Wal, 2010) to measure cognitive flexibility, and the Clance Impostor Phenomenon Scale (CIPS; Clance, 1985) to assess impostor feelings. Data were analyzed using SPSS version 27 for descriptive and correlation analyses and AMOS version 21 for structural equation modeling (SEM). Model fit was evaluated through indices including χ²/df, GFI, AGFI, CFI, TLI, and RMSEA, with significance determined at p < .05. Results revealed significant relationships among the study variables. Perfectionism was positively correlated with impostor feelings (r = .57, p < .001), while cognitive flexibility was negatively correlated with both perfectionism (r = −.48, p < .001) and impostor feelings (r = −.53, p < .001). The SEM analysis demonstrated excellent model fit (χ²/df = 1.48, GFI = .95, CFI = .97, RMSEA = .035). Perfectionism exerted a significant direct effect on impostor feelings (β = 0.38, p < .001) and a negative effect on cognitive flexibility (β = −0.41, p < .001). Cognitive flexibility significantly predicted lower impostor feelings (β = −0.33, p < .001) and partially mediated the perfectionism–impostor relationship (indirect β = 0.13, p < .01). The findings suggest that cognitive flexibility functions as a protective cognitive mechanism that mitigates the negative impact of perfectionism on impostor feelings. Enhancing cognitive flexibility may therefore reduce self-doubt and promote adaptive coping among perfectionistic female students.